2023
DOI: 10.3390/ijms24043111
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol and Its Potential Uses on Intestinal and Gastrointestinal Disease

Abstract: In recent years, the phytoconstituents of foods in the Mediterranean diet (MD) have been the subject of several studies for their beneficial effects on human health. The traditional MD is described as a diet heavy in vegetable oils, fruits, nuts, and fish. The most studied element of MD is undoubtedly olive oil due precisely to its beneficial properties that make it an object of interest. Several studies have attributed these protective effects to hydroxytyrosol (HT), the main polyphenol contained in olive oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 145 publications
0
9
0
Order By: Relevance
“…Clinical and animal experimental studies have demonstrated that stress-related hormones of CORT directly cause liver injury. 3,8,9 Furthermore, chronic accumulation of CORT and perturbations to the oxidative and anti-oxidative balance can increase levels of proinflammatory cytokines such as IL-6, TNF-α and IL-1β, 10,25 which have been shown to promote the processes of liver injury. 19 Therefore, the efficacy of HT in preventing liver injury in CUMS mice may be mediated by decreasing oxidative stress, reducing the accumulation of CORT, and reducing the level of pro-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and animal experimental studies have demonstrated that stress-related hormones of CORT directly cause liver injury. 3,8,9 Furthermore, chronic accumulation of CORT and perturbations to the oxidative and anti-oxidative balance can increase levels of proinflammatory cytokines such as IL-6, TNF-α and IL-1β, 10,25 which have been shown to promote the processes of liver injury. 19 Therefore, the efficacy of HT in preventing liver injury in CUMS mice may be mediated by decreasing oxidative stress, reducing the accumulation of CORT, and reducing the level of pro-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxytyrosol (HT), a phenolic extra-virgin olive oil compound used as a food supplement, has been recognized to offer beneficial effects such as antioxidant, anti-inflammatory, anti-proliferative, anti-microbial, and anti-atherogenic effects. 9,10 Recently, HT has been reported to exhibit potential use for liver protection in ethanol-induced liver injury, 11 liver ischemia/reperfusion injury, 12 NAFLD, 13 and lipopolysaccharides-induced acute liver injury. 14 Meanwhile, our previous research showed that HT regulates hypothalamic-pituitaryadrenal (HPA) axis function and pro-inflammatory cytokine release, thus ameliorating chronic stress-induced depressive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This bioactivity is especially significant for their impact on the treatment and prevention of non-communicable diseases, such as obesity [ 18 ], diabetes [ 19 ], and inflammatory intestinal diseases [ 20 , 21 , 22 ], pathologies whose incidence has increased dramatically during the last decades. More specifically, hydroxytyrosol and oleuropein, the most abundant phenolic compounds in olive leaves, have shown an anti-inflammatory effect on intestinal conditions, such as ulcerative colitis [ 23 , 24 , 25 ]. Additionally, these health benefits have been related to the impact of these compounds on the colonic microbiota, modulating gut microbial composition, promoting probiotic bacteria while inhibiting pathogenic strains [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding antioxidant activity, the use of polyphenolic powder from olive mill wastewater in broiler chicken drinking water increased antioxidant capacity and reduced oxidative stress [ 15 ]. Furthermore, HT absorption and metabolism are characterized as a fast process of binding to lipoproteins acting as cardiovascular and antioxidant protectors and then distribution in several organs, including the liver, where HT is oxidized, methylated, and methylated–oxidized [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%